2001
DOI: 10.1116/1.1377589
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence from ZnTe:Yb films grown on (100) GaAs by molecular beam epitaxy

Abstract: Photoluminescence of Ga-doped ZnO film grown on c -Al 2 O 3 (0001) by plasma-assisted molecular beam epitaxyYb-doped ZnTe layers grown on GaAs substrates have been obtained using molecular beam epitaxy. A study of photoluminescence of ZnTe:Yb/GaAs structures is performed. It is demonstrated that Yb can be rendered optically active in ZnTe if it is incorporated in three-component complexes which consist of ytterbium, oxygen, and some of background impurities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…As for the physical method, MBE and PLD are both applied to obtain the RE‐doped TMDs. Yb‐doped ZnTe layers have been fabricated using MBE on GaAs substrates . The 1‐μm ZnTe buffer layer was deposited before the introduction of 1.5 μm Yb‐doped ZnTe layers.…”
Section: Materials Classification and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…As for the physical method, MBE and PLD are both applied to obtain the RE‐doped TMDs. Yb‐doped ZnTe layers have been fabricated using MBE on GaAs substrates . The 1‐μm ZnTe buffer layer was deposited before the introduction of 1.5 μm Yb‐doped ZnTe layers.…”
Section: Materials Classification and Synthesismentioning
confidence: 99%
“…The striking red‐shift of the PL peaks for the Eu 3+ arose, compared with the bulk or nanoparticle materials containing Eu 3+ , indicated that the crystal field surrounding Eu ions in the 2D single layer of MoS 2 with a higher anisotropy can efficiently distort the degenerate orbitals (Figure ‐). High‐quality ZnTe layers with Yb doping were prepared and the Yb dopant showed optically active if it was associated with other impurities . The oxygen probably took part in the energy transfer process.…”
Section: Applicationsmentioning
confidence: 99%
“…Basing upon our data on Yb 3þ ion emission activation an additional oxygen implantation into the MBE Yb-doped ZnTe samples and subsequent annealing were performed [2]. The oxygen was implanted into ZnTe : Yb structures using a set of energies and doses to produce flat profile of dopants up to the depth of 0.5 mm with concentration in the range of 1 Â 10 17 -1 Â 10 20 cm -3 at room temperature.…”
mentioning
confidence: 99%
“…A strong temperature stable Yb-related luminescence was observed in more than 60 samples. The detail of the sample preparation procedure is given in [2]. It was shown that the optimal Yb and oxygen concentrations are $5 Â 10 18 cm -3 and $3 Â 10 19 cm -3 , respectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation